Review article developing safety and enjoyment factors in karst cave tourism model: review discussing the model, factors and results - Trio Yonathan Teja Kusuma; Susy Susmartini; Bambang Suhardi; Lobes Herdiman (Cogent Social Sciences)
Indonesia has a karst area as a geosite reaching 154,000 km2. Indonesia’s vast karst areas create extensive cave networks developed for geotourism, making cave tours a popular activity, though they pose risks of excessive exploitation, environmental destruction, and high-risk tourism. The aim of this research is to determine the factors used to develop karst geotourism models in academic research over the last decade and to identify indicators of safety and enjoyment factors in developing karst geotourism models. The systematic literature review method uses the PRISMA method and bibliometric analysis uses Vosviewer. The data source was obtained from Scopus for the 2018–2023 period. The results obtained were 268 articles, then data reduction was carried out and 39 journals were obtained for review. The theory used in this systematic literature review is the theory of sustainable tourism and found that influential factors in the development of sustainable geotourism models include scientific, educational, esthetic, recreational/touristic, functional, vulnerability, cultural, economic, socio-political, biological and anthropogenic. However, safety and enjoyment factors in sustainable geotourism models are rarely discussed, despite their role in shaping destination image and tourist experience. These factors are crucial, especially in fragile karst geotourism.